Filgotinib, a JAK1 Inhibitor, Has No Effect on QT Interval in Healthy Subjects. Issue 1 (2nd December 2019) - Anderson, Kacey; Xin, Yan; Zheng, Hao; Yun, Chohee; Kwan, Ellen; Qin, Ann; Namour, Florence; Kearney, Brian P.; Mathias, Anita
Abstract: Filgotinib, a selective inhibitor of Janus kinase 1, is being developed for the treatment of chronic inflammatory diseases. Electrocardiograms evaluated the effect of filgotinib on the corrected QT (QTc) interval in 52 healthy subjects who received each of 4 treatments: filgotinib 200 mg (therapeutic dose), 450 mg (supratherapeutic dose), and placebo, each administered once daily for 7 days, and a single dose of moxifloxacin 400 mg (positive control). Plasma samples were collected for pharmacokinetic analysis. The QTc interval was calculated using Fridericia's correction factor (QTcF) or an individual correction factor (QTcI). The relationship between plasma concentrations of filgotinib and its major metabolite and time‐matched, baseline‐adjusted, placebo‐corrected QTc (ΔΔQTc) was evaluated. Filgotinib did not prolong QTcF or QTcI and using an appropriate mixed‐effect model, the upper limit of the 2‐sided 90% confidence interval for ΔΔQTc for each filgotinib dose (200 and 450 mg) remained below 10 milliseconds at all postdose time points. There were no clinically relevant relationships between QTc interval and plasma concentrations of filgotinib or its major metabolite. Filgotinib, administered at 200 or 450 mg, was generally well tolerated. Results of this thorough QT study demonstrate that filgotinib and its major metabolite are not associated with QTc interval prolongation.